2010
DOI: 10.1111/j.1398-9995.2009.02181.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐series nasal epithelial transcriptomics during natural pollen exposure in healthy subjects and allergic patients

Abstract: We showed that birch pollen allergen causes a defence response in healthy subjects, but not in allergic subjects. Instead, allergic patients actively transport pollen allergen through the epithelium to tissue mast cells. Our study showed that new hypotheses can arise from the application of discovery driven methodologies. To understand complex multifactorial diseases, such as type I hypersensitivity, this kind of hypotheses might be worth further analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…A hypothesis-free approach in order to analyze the differences between respiratory epithelial swabs from allergic and healthy subjects during the asymptomatic winter period [45,46,54], 182 significantly differentially expressed transcripts (and thus proteins after converting them to corresponding proteins) in between these two groups could be detected. Twenty-two epithelial cell surface receptors displayed enhanced expression levels in allergic compared to healthy subjects and eight out of them were found in lipid rafts/caveolae according to manual PubMed literature search (Table 3, [45]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypothesis-free approach in order to analyze the differences between respiratory epithelial swabs from allergic and healthy subjects during the asymptomatic winter period [45,46,54], 182 significantly differentially expressed transcripts (and thus proteins after converting them to corresponding proteins) in between these two groups could be detected. Twenty-two epithelial cell surface receptors displayed enhanced expression levels in allergic compared to healthy subjects and eight out of them were found in lipid rafts/caveolae according to manual PubMed literature search (Table 3, [45]).…”
Section: Introductionmentioning
confidence: 99%
“…The first nasal epithelial specimens were obtained in February when all subjects were symptom-free and the following four nasal epithelial cell swabs were collected from each subject at weekly intervals starting in mid-April when the birch pollen season in Finland begins. While the healthy subjects remained totally symptomless throughout this whole period of time the allergic subjects began to have symptoms already in April, which worsened along with the birch pollen season [54]. …”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies in humans have identified several loci associated with asthma in multiple study populations (9)(10)(11)(12)(13)(14), and a genome-wide association study of allergic rhinitis also identified multiple loci, some of which overlap with asthma loci (e.g., LRRC32, HLA-G, and TSLP) (15). Several studies have also identified gene expression profiles that differentiate normal versus AAD in affected tissue (16)(17)(18)(19)(20)(21).…”
Section: Clinical Relevancementioning
confidence: 99%
“…These data are very similar to recently published results showing 8 of 33 patients (24%) with very low specific IgE radioallergosorbent test (RAST) value for ragweed but positive history and SPT (Stokes et al, 2005). These findings imply that allergic and/or non-allergic components of pollen can enhance or even induce allergy-like symptoms even in the absence of specific IgE, e.g., by directly activating MCs in the skin or mucosa (Mattila et al, 2010). Indeed, extracts of birch pollen have previously been shown to directly activate neutrophils, eosinophils, and dendritic cells (TraidlHoffmann et al, 2002(TraidlHoffmann et al, , 2005Plotz et al, 2004), and ragweed pollen extracts can reportedly induce IgEindependent histamine release from rat basophilic leukemia cells (Chodaczek et al, 2009).…”
mentioning
confidence: 94%